Potential induced along a pipeline during geomagnetic storms and geoelectric coast effect - Lucca, Giovanni (Contributions to Geophysics and Geodesy, 2026)
The paper proposes a calculation method for the assessment of the induced potential along a pipeline, located nearby a coastline, due to the geomagnetic induction occurring during geomagnetic storms. The algorithm is based on the generalized thin sheet model to describe the inducing geoelectric field and on the transmission line model with lumped parameters to describe the pipeline under the influence of the geoelectric field which is supposed to have a generic polarization. In particular, the proposed calculation method allows for the assessment of the potential profile that can be generated along the pipeline and for the identification of the zones, along the pipeline layout, that are more exposed to the occurrence of high electric potentials. We remind that the overpotentials generated along the infrastructure can interfere with the pipeline cathodic protection and with the electrical survey apparatuses, thus affecting their correct functioning and so increasing the corrosion risk. Therefore, this model can be an aid, also at the design stage of a new infrastructure, able to individuate the riskiest zones, along the pipeline layout, subjected to the highest induced potentials so allowing to minimize the threaten represented by geomagnetic storms. The peculiarity and novelty of the paper, differently from previous works, is the taken account of the geoelectric coast effect in the assessment of the induced potential profile along the pipeline route by means of an approach that is based on the generalized thin sheet model under a generic state of polarization of the inducing geomagnetic field.